Histological, chemical and behavioural evidence of pedal communication in brown bears - Sergiel, Agnieszka (Sci Rep, 2017)
Most mammals rely upon scent for intraspecific communication. As most bear species have large home ranges and are non-territorial, scent deposit while walking could be an effective way to communicate with conspecifics. Here, we investigate the existence of pedal glands in brown bears and their role in chemical communication from a histological, biochemical and behavioural perspective. We found eccrine glands in footpads, and prominent apocrine and sebaceous glands in the interdigital, metacarpal and metatarsal skin sections. Pedal scent contained 26 compounds including carboxylic acids, important constituents of mammalian secretions. Six of these compounds were exclusive for males. Finally, we describe a specific marking gait recorded in the field, mostly performed by males. Our study supports the existence of chemical communication through pedal marking in brown bears and suggests sex-coding potential of pedal scent.